Autonomous remote measurement system for industrial fans as a result of an innovative project stage - Piwowarski, Marian; Czyżewicz, Jacek; Ziemiański, Paweł; Bortkiewicz, Mateusz; Laszuk, Krzysztof; Galara, Ireneusz; Pawłowska, Marta; Cybulski , Karol (Instal, 2022)
The article presents the process of building and testing a remote, fully autonomous system for measuring fan operating parameters. The process was completed as part of the first stage of an innovative project. The paper includes detailed steps of constructing a system for collecting and processing measurement data from fans installed in their operating conditions and the results of their analysis. In particular, the measurement infrastructure was developed and implemented, including determining a set of necessary measurement equipment. Measuring equipment was installed in selected fans installations. Systems have been implemented that allow for continuous measurement of installation parameters and remote data transmission to the server, followed by an ongoing analysis and selection of the collected data for use in the modeling and diagnostics process. A satisfactory degree of correlation between the selected parameters measured in actual operating conditions and the characteristics of the fan and the installation was verified experimentally. Its indication was finding 4 statistically significant parameters at the confidence level of 95%.